2012
DOI: 10.1111/j.1750-8606.2011.00228.x
|View full text |Cite
|
Sign up to set email alerts
|

Social Change and Adolescent Developmental Tasks: The Case of Postcommunist Europe

Abstract: The radical political transformations of the 1990s in many countries of Central and Eastern Europe and the former Soviet Union, overlaid by effects of globalization and related economic crises, have had an effect on young people, particularly by changing contexts relevant for psychosocial development. According to research on major developmental tasks in adolescence, young people benefited from new freedoms, such as the open borders and advanced communication technologies, but they also faced new economic unce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 82 publications
0
18
0
Order By: Relevance
“…Fifth, it must be considered that our finding that warm parenting predicts adolescents' political trust and the similar finding by Gniewosz et al (2009) both come from post-communist areas where the role of state has become weakened, which shifted the responsibility for socialization between family and state to families (Tomasik & Silbereisen, 2012). Therefore, further studies are needed to confirm whether the association has the same strength in other sociopolitical contexts.…”
Section: Limitationsmentioning
confidence: 65%
“…Fifth, it must be considered that our finding that warm parenting predicts adolescents' political trust and the similar finding by Gniewosz et al (2009) both come from post-communist areas where the role of state has become weakened, which shifted the responsibility for socialization between family and state to families (Tomasik & Silbereisen, 2012). Therefore, further studies are needed to confirm whether the association has the same strength in other sociopolitical contexts.…”
Section: Limitationsmentioning
confidence: 65%
“…Raised under one set of rules, they had to negotiate the transition to adulthood and the selfdetermination that democracy offered within the context of economic uncertainties (Tomasik & Silbereisen, 2012). Insofar as trust in others is premised on a sense of security, the anxiety that many youth were feeling provided neither a solid foundation for reaching out and helping others nor fertile ground for nurturing social trust in fellow citizens (Flanagan, 2003).…”
Section: Downloaded By [Fu Berlin] At 06:26 15 May 2015mentioning
confidence: 99%
“…We fitted the same regression model for two polities at the same time and compared relationship patterns and regression coefficients between them. Three outcome variables were predicted all at once with maximum likelihood estimation with robust standard errors (MLR) using Mplus 7.1 (Muthén & Muthén, 1998-2012. To compare regression coefficients between two types of polities, we conducted the Wald test, which provides similar results as the likelihood ratio different test.…”
Section: Analysesmentioning
confidence: 99%
“…A review of relevant research have shown that it is not usually the substance or appreciation of the developmental tasks that are affected by social change, except perhaps for the new role of public selfpresentation in modern mass media, but that the accustomed steps toward those goals may lose their relevance in the changed societal structure (Tomasik and Silbereisen, 2012). A review of relevant research have shown that it is not usually the substance or appreciation of the developmental tasks that are affected by social change, except perhaps for the new role of public selfpresentation in modern mass media, but that the accustomed steps toward those goals may lose their relevance in the changed societal structure (Tomasik and Silbereisen, 2012).…”
Section: Polyvalent Effectsmentioning
confidence: 99%
“…While social change is obviously not a new phenomenon, many believe that the pace of social change has been accelerating over the recent decades (see Tomasik and Silbereisen, 2012). While social change is obviously not a new phenomenon, many believe that the pace of social change has been accelerating over the recent decades (see Tomasik and Silbereisen, 2012).…”
mentioning
confidence: 99%